Causal Associations between Lipid Profiles And Risk of Gallstone Disease - Santosh Mishra,; Divas Thapa,; Nabin Pokhrel,; Shreeyanshu Parajuli,; Manab Tiwari,; Aaditya Bhardwaj,; Manshi Aryal, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTIONGallstone disease (GSD) is a significant global health concern with multifactorial etiology. Dyslipidemia, characterized by altered levels of triglycerides (TGs), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and total cholesterol (TC), is hypothesized to play a critical role in gallstone formation. So, this study aims to explore how changes in lipid profiles affect the risk of gallstone disease, focusing on the role of altered lipid metabolism in gallstone formation.MATERIAL AND METHODSThis prospective observational study was conducted at UCMS-TH on 100 patients with GSD, confirmed with ultrasonography of abdomen and pelvis, between May, 2024 to October, 2024. Lipid profiles were assessed, and demographic and clinical data were collected. Patients were grouped based on the presence of single or multiple gallstones for comparative analysis.RESULTSThe mean levels of TGs, HDL, LDL, and TC in the study population were 156.85 mg/dL, 40.68 mg/dL, 115.14 mg/dL, and 190.11 mg/dL, respectively. Patients with multiple gallstones exhibited slightly higher TGs, TC and LDL levels compared to those with single gallstones.CONCLUSIONElevated TGs, LDL and TC levels were strongly associated with GSD, supporting their role as potential risk factors. Further research is needed to establish causality and evaluate the impact of lipid management in gallstone prevention.